2002
DOI: 10.1046/j.1524-475x.2002.10308.x
|View full text |Cite
|
Sign up to set email alerts
|

Early healing events in a porcine model of contaminated wounds: effects of nanocrystalline silver on matrix metalloproteinases, cell apoptosis, and healing

Abstract: A porcine model of wound healing was employed to examine the impact of nanocrystalline silver-coated dressings on specific wound healing events. Full-thickness wounds were created on the backs of pigs, contaminated with an experimental inoculum containing Pseudomonas aeruginosa, Fusobacterium sp., and coagulase-negative staphylococci, and covered with dressing products either containing silver or not. Nanocrystalline silver-coated dressings promoted rapid wound healing, particularly during the first several da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
225
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(246 citation statements)
references
References 35 publications
13
225
0
5
Order By: Relevance
“…Silver may also possess anti-inflammatory properties; for example, studies have shown increased neutrophil apoptosis, reduced matrix metalloproteinase activity, reduced tumor necrosis factor-alpha levels, and more rapid healing in wounds dressed with silver [15][16][17][18][19]. Silver must be in a soluble, uncharged (Ag 0 ) or metallic (Ag +1 ) form to provide these biological effects [7].…”
Section: Wsrc-ms-2005-00051mentioning
confidence: 99%
“…Silver may also possess anti-inflammatory properties; for example, studies have shown increased neutrophil apoptosis, reduced matrix metalloproteinase activity, reduced tumor necrosis factor-alpha levels, and more rapid healing in wounds dressed with silver [15][16][17][18][19]. Silver must be in a soluble, uncharged (Ag 0 ) or metallic (Ag +1 ) form to provide these biological effects [7].…”
Section: Wsrc-ms-2005-00051mentioning
confidence: 99%
“…Bacterial colonization and subsequent infection can interfere with the wound healing process by producing various substances (e.g., toxins, proteases and proinflammatory molecules) which may cause an excessive and prolonged inflammatory response of the host tissues [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Idealantimicrobial dressings should have a number of key attributes, including provision of a moist environment to enhance healing [20], and broad-spectrum antimicrobial activity, including activity against antibioticresistant bacteria [e.g., methicillin-resistant Staphylococcus aureus (MRSA)] [16][17][18][19]. A recent resurgence of the use of silver-based dressings has been ascribed to their broadspectrum antibacterial activity, as well as to a less possibility for inducing bacterial resistance than antibiotics [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Silver-based technologies added benefits by down-regulating tissue inhibitors of metalloproteinase to levels that facilitate wound healing [10].the results of several studies suggest that nanocrystalline silver specifically may play a role in altering or compressing the inflammatory events in wounds and facilitating the early phases of wound healing. These benefits are associated with reduced local matrix metalloproteinase levels and enhanced cellular apoptosis [12,13]. 3-Zinc metabolism was up regulated, implying increases epithelialization [14,15].…”
Section: Discussionmentioning
confidence: 99%